2017
DOI: 10.1186/s12858-017-0079-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased enzymatic hydrolysis of sugarcane bagasse by a novel glucose- and xylose-stimulated β-glucosidase from Anoxybacillus flavithermus subsp. yunnanensis E13T

Abstract: Backgroundβ-Glucosidase is claimed as a key enzyme in cellulose hydrolysis. The cellulosic fibers are usually entrapped with hemicelluloses containing xylose. So there is ongoing interest in searching for glucose- and xylose-stimulated β-glucosidases to increase the efficiency of hydrolysis of cellulosic biomass.ResultsA thermostable β-glucosidase gene (Bglp) was cloned from Anoxybacillus flavithermus subsp. yunnanensis E13T and characterized. Optimal enzyme activity was observed at 60 °C and pH 7.0. Bglp was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…With the increasing of glucose, the enzyme activity of Dth3 was gradually inhibited, with a K i of over 3 M glucose, which was higher than that from Anoxybacillus flavithermus subsp. yunnanensis, Thermotoga thermarum, and other reported β- glucosidases [31,44,45]. In addition, the activity of xylose has not been reported yet.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…With the increasing of glucose, the enzyme activity of Dth3 was gradually inhibited, with a K i of over 3 M glucose, which was higher than that from Anoxybacillus flavithermus subsp. yunnanensis, Thermotoga thermarum, and other reported β- glucosidases [31,44,45]. In addition, the activity of xylose has not been reported yet.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, most β-glucosidases and β-xylosidases are sensitive to glucose and xylose, and few β-glucosidases and β-xylosidases are tolerant and stimulated by both glucose and xylose [30,31]. As we all know, in most industries, application of β-glucosidases and β-xylosidases with glucose and xylose tolerance and stimulation can improve the efficiency of substrate hydrolyzation [32][33][34].…”
Section: Effect Of Sugars On the Activities Of Recombinant Dth3 And Xmentioning
confidence: 99%
“…shown that a thermostable β-glucosidase produced by Anoxybacillus flavithermus isolated from Tengchong hot spring in Yunnan, China was highly effective in hydrolyzing cellulose when used with a commercial cellulase product (Celluclast®, Novozymes) (Liu et al, 2017). The authors found that the cellulose content of sugarcane bagasse decreased by 25% when only Celluclast® was used, but when β-glucosidase (50 µg/g sugarcane bagasse) was used synergistically with Celluclast®, a 48% decrease was observed (Liu et al, 2017 & Dijkhuizen, 2002;Whitehurst & Van Oort, 2009). Thermostable α-glucosidase from Thermococcus hydrothermalis has been used with α-amylase and pullulanase for starch processing into glucose syrup (Legin, Copinet, & Duchiron, 1998).…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…β‐glucosidase is an important enzyme for the processing of sugarcane bagasse, the dry pulpy fibrous residue after juice extraction. It has been shown that a thermostable β‐glucosidase produced by Anoxybacillus flavithermus isolated from Tengchong hot spring in Yunnan, China was highly effective in hydrolyzing cellulose when used with a commercial cellulase product (Celluclast®, Novozymes) (Liu et al., 2017). The authors found that the cellulose content of sugarcane bagasse decreased by 25% when only Celluclast® was used, but when β‐glucosidase (50 µg/g sugarcane bagasse) was used synergistically with Celluclast®, a 48% decrease was observed (Liu et al., 2017).…”
Section: Categories and Applications Of Food Enzymes From Extremophilesmentioning
confidence: 99%
“…For achieving the goal of economic biofuel production, many researchers have been working on different fungal and bacterial strains so as to obtain an effective cellulolytic fungal or bacterial β-glucosidase [73]. Liu et al [74] reported on the increased hydrolysis of sugarcane bagasse with the help of BGL produced from Anoxybacillus flavithermus subsp. yunnanensis E13 T .…”
Section: Industrial Importance Of β-Glucosidase In Biofuelsmentioning
confidence: 99%